Evaluasi Penerapan Sistem Pengendalian Intern pada Kualitas Laporan Keuangan KPP Bea Cukai X - Valentina Amalia Putri; Mochammad Ilyas Junjunan; Binti Shofiatul Jannah (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
This study aims to analyze the application of the internal control system based on the COSO framework at the X Customs Supervision and Service Office in an effort to improve the quality of financial statements in the midst of rampant cases of smuggling illegal goods that harm the state so it is important to implement a comprehensive internal control system. The research method used is descriptive qualitative. Data collection is done through interviews and documentation through the stages of collection, data production, data presentation and conclusion drawing. The COSO framework is used as a reference in analyzing five internal control components: control environment, risk assessment, control activities, information and communication, and monitoring. Evaluation of the implementation of the internal control system on the quality of Customs and Excise financial reports is necessary for the development of a comprehensive research methodology to measure the effectiveness of the internal control system and its impact on the quality, reliability and transparency of financial reports within the Customs and Excise. The results showed that X Customs Supervision and Service Office has implemented internal control in accordance with the COSO framework, by developing a systematic and comprehensive monitoring mechanism.